Raincoats or riches? Contextualising vararfeldir through multi-perspective experiments - Hopkin, Julia (Archaeological Textiles Review, 2021)
Fleece pile cloaks or vararfeldir feature regularly in early medieval (870 CE to 1200 CE) Icelandic textual sources as a staple of north Atlantic trade. Archaeological finds and reconstruction projects have provided numerous insights. However, few studies have investigated how vararfeldir were used, or why they were produced and traded so extensively when other materials were available. This project used controlled experiments to compare the properties of reconstructed vararfeldir with contemporary materials, while a public consultation provided alternative perspectives. The resulting data suggest that the demand for vararfeldir may have been driven by more complex forces than previously assumed, including specific practical needs, production advantages and subjective concepts. This provides broader insights into the perceptions and priorities of early medieval society and suggests numerous avenues for future investigation. The results highlight the potential for multiperspective, contextualised investigations to broaden understanding of textiles as societally-embedded technologies.